ANALISIS TEKNIK DASAR LARI SPRINT 80 METER ATLET PUTRI PASI KOTA BANJARBARU - Muhammad Abdussalam; Akhmad Amirudin; Perdinanto (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
This exploration means to break down the execution of run running among competitors who are individuals from the Indonesian Sports Affiliation (PASI) in Banjarbaru. Observational results show that many sprint runners have weaknesses in their fundamental techniques. This study uses a descriptive method to evaluate the athletic sprint running abilities of PASI Banjarbaru. Data was obtained through test analysis and measurement. The population consists of 12 athletes, with a sample selected based on purposive sampling criteria. The research findings indicate that the implementation of sprint running by female athletes of PASI Banjarbaru, classified as